Mucosal Exposure to Cigarette Components Induces Intestinal Inflammation and Alters Antimicrobial Response in Mice - Berkowitz, Loni; Pardo-Roa, Catalina; Salazar, Geraldyne A.; Salazar-Echegarai, Francisco; Miranda, José P.; Ramírez, Gigliola; Chávez, José L.; Kalergis, Alexis M.; Bueno, Susan M.; Álvarez-Lobos, Manuel (Frontiers in Immunology, 2019)
The main environmental risk factor associated with the development of Crohn's disease (CD) is cigarette smoking. Although the mechanism is still unknown, some studies have shown that cigarette exposure affects the intestinal barrier of the small bowel. Among the factors that may be involved in this process are Paneth cells. These specialized epithelial cells are located into the small intestine, and they are able to secrete antimicrobial peptides, having an essential role in the control of the growth of microorganisms. Alterations in its function are associated with inflammatory processes, such as CD. To study how cigarette components impact ileum homeostasis and Paneth cells integrity, we used intragastric administration of cigarette smoke condensate (CSC) in mice. Our results showed that inflammation was triggered after mucosal exposure of CSC, which induced particular alterations in Paneth cells granules, antimicrobial peptide production and a reduction of bactericidal capacity. In fact, exposure to CSC generated an imbalance in the fecal bacterial population and increased the susceptibility of mice to develop ileal damage in response to bacterial infection. Moreover, our results obtained in mice unable to produce interleukin 10 (IL-10-/- mice) suggest that CSC treatment can induce a symptomatic enterocolitis with a pathological inflammation in genetically susceptible individuals.